Do supersonic aircraft avoid contrails? - Stenke, A.; Grewe, V.; Pechtl, S. (HAL CCSD, 2007)
International audience The impact of a potential future fleet of supersonic aircraft on contrail coverage and contrail radiative forcing is investigated by means of simulations with the general circulation model ECHAM4.L39(DLR) including a contrail parameterization. The model simulations consider air traffic inventories of a subsonic fleet and of a combined fleet of sub- and supersonic aircraft for the years 2025 and 2050, respectively. In case of the combined fleet, part of the subsonic fleet is replaced by supersonic aircraft. Supersonic aircraft fly at higher cruise levels (18 to 20 km) than subsonic aircraft (10 to 12 km). The different ambient meteorological conditions in terms of temperature and humidity affect the formation of contrails. At subsonic cruise levels, the combined air traffic scenario reveals a reduction in contrail cover in northern extratropics, especially over the North Atlantic and Pacific. At supersonic flight levels, contrail formation is mainly restricted to tropical regions. The northern extratropical stratosphere is only in winter cold enough for the formation of contrails. Total contrail coverage is only marginally affected by the shift in flight altitude. The model simulations indicate a global annual mean contrail cover of 0.372% for the subsonic and 0.366% for the combined fleet in 2050, respectively. The simulated contrail radiative forcing is most closely correlated to the total contrail cover, although contrails in the tropical lower stratosphere are found to be optically thinner than contrails in the extratropical upper troposphere. The global annual mean contrail radiative forcing in 2050 (2025) amounts to 24.7 mW m ?2 (9.4 mW m ?2 ) for the subsonic fleet and 24.2 mW m ?2 (9.3 mW m ?2 ) for the combined fleet. A reduced supersonic cruise speed (Mach 1.6 instead of Mach 2.0) leads to a downward shift in contrail cover, but does not affect global mean total contrail cover and contrail radiative forcing. Hence the partial substitution of subsonic air traffic leads to a shift ...